ANALISIS MANAJEMEN LOGISTIK OBAT DI INSTALASI FARMASI DINAS KESEHATAN KOTA MANADO TAHUN 2020 - Nur Azmi F. Taha; Widya Astuty Lolo; Gerald Rundengan (PHARMACON, 2021)
ABSTRACTDrug logistics management is a process of activities in the aspects of planning, procurement, storage, distribution and elimination of drugs. The purpose of this research is to know the description of the drug logistics management process at the Pharmaceutical Installation of Manado City Health Office as well as the availability of medicines needed by public health center from the implementation of drug logistics management. This research uses qualitative descriptive method with data retrieval conducted through in-depth and open in-depth in-person interviews of informants and observations. The results of the research obtained show that human resources in the management of drug logistics in pharmaceutical installations are insufficient in the process of drug logistics management. The source of funds in the drug management process comes from State Budget and Regional Budget. The methods used in drug planning are combination methods, disease pattern methods and consumption methods. Procurement is done with an e-catalogue system. The storage of the drug is stored in a pharmaceutical warehouse and arranged alphabetically and dosage form. Then for the distribution of drugs is done every month based on Usage Sheet And Drug Request Sheet. As for the elimination of the drug is done every 5 months before expired date by making news event removal of the drug. The conclusion of this study is the management of drug logistics in the pharmaceutical installation of the manado city health office, especially human resources is still insufficient because there is no acceptance of civil servants so that pharmaceutical workers are lacking. The process of managing drugs to puskesmas is also not fully fulfilled so that the puskesmas must equip themselves by using capitation funds from National Health Insurance.Keyword: Logistics Management, Pharmaceutical Installation, Health OfficeABSTRAKManajemen logistik obat merupakan proses kegiatan dalam aspek perencanaan, pengadaan, penyimpanan, pendistribusian dan penghapusan obat. Tujuan dari penelitian ini yaitu untuk mengetahui gambaran dari proses manajemen logistik obat di Instalasi Farmasi Dinas Kesehatan Kota Manado serta tersedianya obat yang dibutuhkan puskesmas dari pelaksanaan manajemen logistik obat. Penelitian ini menggunakan metode deskriptif kualitatif dengan pengambilan data dilakukan melalui wawancara langsung secara mendalam dan terbuka terhadap informan dan observasi. Hasil penelitian yang diperoleh menunjukkan bahwa sumber daya manusia dalam manajemen logistik obat di instalasi farmasi berjumlah 3 orang Apoteker, 2 orang asisten Apoteker dan 9 orang THL. Sumber dana dalam proses pengelolaan obat berasal dari dana APBD dan APBN. Metode yang dipakai dalam perencanaan obat yaitu metode kombinasi, metode pola penyakit dan metode konsumsi. Pengadaan dilakukan dengan sistem e-catalogue. Penyimpanan obat disimpan dalam gudang farmasi dan disusun secara alfabet dan bentuk sediaan. Kemudian untuk pendsitribusian obat dilakukan setiap bulan berdasarkan LPLPO. Adapun untuk penghapusan obat dilakukan setiap 5 bulan sebelum expired date dengan membuat berita acara penghapusan obat. Kesimpulan dari penelitian ini yaitu manajemen logistik obat di instalasi farmasi dinas kesehatan kota manado khususnya SDM masih belum mencukupi karena belum adanya pemenerimaan pegawai negeri sehingga tenaga kefarmasian kurang. Proses pengelolaan obat ke puskesmas juga belum sepenuhnya tercukupi sehingga puskesmas harus melengkapi sendiri dengan menggunakan dana kapitasi dari JKN.Â Kata Kunci: Manajemen Logistik, Instalasi Farmasi, Dinas Kesehatan